Learning strategies and academic performance in the subject Mathematical Analysis II - Chávez Arias, Leticia Enriqueta (2018)
The objective was to determine the relationship between learning strategies for students at ESPOCH’s School of Mechanical Engineering and the academic performance in Mathematical Analysis II by analyzing a sample population of 82 students. This research was not experimental, it was quantitative-qualitative and of the descriptive-correlational type. The CEVEAPEU questionnaire was used to identify learning strategies and final grades in order to measure academic performance. 52% of students were underperformers and there were no high performers. Nineteen learning strategies are predominant. Four strategies significantly impinged on academic performance. Only the «planning» learning strategy was not used by low performing students. The research hypothesis is rejected and it is recommended to conduct a pilot study on the «planning» learning strategy as a predictor of academic performance.